PENGARUH MEREK DAN CITRA DIRI TERHADAP KEPUASAN KONSUMEN PRODUK TELEPON SELULER DI KOTAMADYA YOGYAKARTA - Wendri Rusli (Jurnal Riset Manajemen dan Bisnis, 2011)
This study aims to analyze the effect of brand preference and self image congruen-cy on customers satisfaction using seluler's telephonic product. This study uses survey methods.  Survey’s region is at Yogyakarta city. The samples used in this study are 100 respondents.  This research uses multiple regression as its data analyses. The results show that self-imagecongruency and brand preference influence on customers satisfaction using seluler's telephonical product. Also, this study indicates that self-image congruency’s role is more dominanton customer satisfaction.Keywords: Self Image Congruency, Brand Preference, Consumer Satisfaction